Research on the saturated/unsaturated seepage laws of ionic rare earth ore under different leaching conditions - Guo, Zhongqun; Liu, Lingfeng; Zhou, Kefan; Wang, Xiaojun; Zhong, Wen (Frontiers in Earth Science, 2023)
Permeability of ore body in leaching mining plays an important role in the efficient development and utilization of ionic rare earth. The saturation seepage test of ionic rare earth ore under different leaching conditions was carried out, and the influence of leaching solution type, concentration and leaching path on the saturation permeability coefficient were revealed. The relationship between water content and matrix suction of ionic rare earth under different leaching conditions was measured by the Geo-Experts pressure plate apparatus. The soil-water characteristic curves under different leaching conditions were obtained. Based on the soil-water characteristic curve model, the unsaturated permeability coefficient function of ionic rare earth under different conditions was studied. The results show that the saturated-unsaturated permeability coefficients of ionic rare earth are pure water, 3% (NH4)2SO4 and 3% MgSO4 in descending order when the type of leaching solution is different. For different concentrations of the leaching solution, when the concentration of (NH4)2SO4 increases from 2% to 5%, the saturated permeability coefficient first increases and then decreases. The matrix suction is an important factor affecting the unsaturated permeability coefficient when the ore body is unsaturated, and the unsaturated permeability coefficient decreases with the increase of the concentration of leaching solution under the same matrix suction. The seepage law is related to the leaching path, and the permeability coefficient increases when leaching under high concentration followed by low concentration, in reverse order, the permeability coefficient decreases. The research results can provide theoretical guidance for the design of injection parameters, and help to improve the theory of in-situ leaching.